Disturbance and flock size changes in Greenland Whitefronted Geese wintering in Ireland - Norriss, D W; Wilson, H J (Wildfowl, 1988)
An index of disturbance was calculated for wintering Greenland White-fronted Goose flocks based on observed disturbance rates and the refuge qualities of feeding ranges. In the three years following protection, changes in status of individual flocks were correlated with their disturbance indices. Agriculture was the single most important source of disturbance and overall rates of disturbance were highest on intensively managed land. However, the smallest indices (most disturbance) were calculated for flocks with few, small feeding sites. Such flocks are generally declining. Consequences of arterial drainage and shooting are discussed. Flocks with better quality feeding ranges are stable or increasing as a result of protection and are not currently threatened by arterial drainage. Prior to protection numerical trends of flocks showed a similar correlation with range quality. Differences in patterns of flock declines and extinctions before and after protection are consistent with known changes in disturbance pressures.